2020
DOI: 10.1186/s12871-020-01030-w
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sevoflurane and propofol on tourniquet-induced endothelial damage: a pilot randomized controlled trial for knee-ligament surgery

Abstract: Background The glycocalyx layer is a key structure in the endothelium. Tourniquet-induced ischemic periods are used during orthopedic surgery, and the reactive oxygen species generated after ischemia-reperfusion may mediate the shedding of the glycocalyx. Here, we describe the effects of tourniquet-induced ischemia-reperfusion and compare the effects of sevoflurane and propofol on the release of endothelial biomarkers after ischemia-reperfusion in knee-ligament surgery. Methods This pilot, single-center, blin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 31 publications
2
21
2
1
Order By: Relevance
“…Our study showed that the serum concentration of syndecan-1 was significantly increased at POD 1 compared to preoperative levels, and that the increase was comparable between patients under volatile anesthesia with sevoflurane/remifentanil and those under TIVA with propofol/remifentanil. Our results further confirmed previous findings indicating that sevoflurane and propofol have similar effects regarding perioperative EG degradation 9 , 10 .…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our study showed that the serum concentration of syndecan-1 was significantly increased at POD 1 compared to preoperative levels, and that the increase was comparable between patients under volatile anesthesia with sevoflurane/remifentanil and those under TIVA with propofol/remifentanil. Our results further confirmed previous findings indicating that sevoflurane and propofol have similar effects regarding perioperative EG degradation 9 , 10 .…”
Section: Discussionsupporting
confidence: 92%
“…Sevoflurane was superior to propofol in protecting the EG from I/R injury in a porcine model 16 . In contrast to experimental results, sevoflurane did not show a better protective effect on the EG than propofol in clinical studies of lung resection surgery and knee-ligament surgery 9 , 10 .…”
Section: Introductioncontrasting
confidence: 96%
See 2 more Smart Citations
“…As mentioned, judicious fluid therapy and use of plasma or albumin have been proposed but require further investigation. Inhalation anaesthesia using sevoflurane has been suggested to have glycocalyx‐protecting or regenerating effects in some studies 39,40 but this was not confirmed by others 22,41 . Other drugs with possible benefits include corticosteroids, antithrombin, heparin and heparinoids 42 .…”
Section: Vascular Permeability and Transvascular Fluid Fluxmentioning
confidence: 99%